Theoretical Concepts for Direct Foreign Investments - Marinov, Velko (Research Papers, 2009)
The study is an attempt to outline the key theoretical models of direct foreign investments. It argues the inability of the traditional theories of the international capital migration (neo-classical, neo-Keynesian and Marxist) to adequately explain this phenomenon of modern business development. The theoretical models of direct foreign investments are represented chronologically, the core being the model of monopolistic advantages of Hymer Kindleberger. Buckley’s and Casson’s internalization models acquire crucial importance at a later stage, as well as the “eclectic” concept of J. Dunning and the model of the competitive advantage of the nations introduced by M. Porter. The paper states the multiple natures of the theoretical models of direct foreign investments and highlights the basis for criticism with regard to those.